Sinergi kepemimpinan visioner, transformasional dan karismatik Kepala MA Al Maarif Singosari dalam implementasi integrasi kurikulum pendidikan islam - Maulani, Kharisma (Maliki Interdisciplinary Journal, 2026)
This study aims to describe the synergy of visionary, transformational, and charismatic leadership demonstrated by the principal of MA Al Maarif Singosari in implementing the integration of Islamic education curriculum. This research employed a qualitative case study approach using in-depth interviews, direct observations, and document analysis. The findings reveal that visionary leadership is reflected in the formulation of strategic policies based on a Qur’anic-oriented vision that guides all institutional programs. Transformational leadership emerges through teacher empowerment, collaborative work culture, learning innovations, and the development of an integrated curriculum. Meanwhile, charismatic leadership is evident in spiritual exemplification, religious habituation, persuasive communication, and consistent moral guidance. The combination of these three leadership styles creates a disciplined, religious, modern, and character-oriented educational environment. The integration of curriculum, professional development of teachers, utilization of technology, management of facilities, and financial transparency are effectively implemented due to strong and well-directed leadership. This study concludes that the synergy of visionary, transformational, and charismatic leadership serves as an effective model for developing Islamic-based educational institutions.